The Impact of the Corona Virus / COVID-19 Quarantine on the Level of Quality of Life among Students of the College of Sports Sciences at Mutah University (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the impact of of the Corona virus/ COVID-19 quarantine on the level of quality of life among students of the College of Sports Sciences at Mutah University. The study sample consisted of (180) male and female students from the College of Sports Sciences at Mutah University, and it was randomly selected from the population of the study. The researcher used the descriptive approach in adopting the survey method with its steps and scientific procedures as it suits the nature of this study. The quality of life scale for university students in the Sultanate of Oman was used, which was codified and developed by Mansi and Kazem (2010). The study addressed the variables of gender, academic level, academic department, and GPA. The results of the study revealed that the Corona virus / COVID-19 quarantine of had an average effect on the dimensions of quality of life for students of the College of Sports Sciences. The results also showed that there are statistically significant differences in the impact of Corona Virus/ COVID-19 quarantine on the level of quality of life for students of the College of Sports Sciences in relation to the variable of gender, in favor of males, and the variable of GPA, in favor of the students with high grades. Based on the results of the study, the study recommends working on developing the personal capabilities of the students of the Colleg of Sports Sciences, which enables them to face any quarantine that may occur in the country. This can be achieved through specialized courses that reduce intimidation, deal with matters rationally, and manage their lives with what is available to them.
Keywords: Corona Virus; Quality of Life; Quarantine